2010
DOI: 10.1136/bmj.c1345
|View full text |Cite
|
Sign up to set email alerts
|

The impact of advance care planning on end of life care in elderly patients: randomised controlled trial

Abstract: Objective To investigate the impact of advance care planning on end of life care in elderly patients.Design Prospective randomised controlled trial.Setting Single centre study in a university hospital in Melbourne, Australia.Participants 309 legally competent medical inpatients aged 80 or more and followed for six months or until death.Interventions Participants were randomised to receive usual care or usual care plus facilitated advance care planning. Advance care planning aimed to assist patients to reflect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

41
1,812
4
40

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,938 publications
(1,897 citation statements)
references
References 40 publications
41
1,812
4
40
Order By: Relevance
“…Models for structuring initiatives to enhance care in the ICU highlight the importance of incorporating goals of care, along with prognosis, into treatment plans [642]. The use of proactive family care conferences to identify advance directives and treatment goals within 72 h of ICU admission has been demonstrated to promote communication and understanding between the patient's family and the treating team; improve family satisfaction; decrease stress, anxiety, and depression in surviving relatives; facilitate end-of-life decision-making; and shorten ICU LOS for patients who die in the ICU [643,644]. Promoting shared-decision-making with patients and families is beneficial in ensuring appropriate care in the ICU and that futile care is avoided [641,645,646].…”
Section: U Setting Goals Of Carementioning
confidence: 99%
“…Models for structuring initiatives to enhance care in the ICU highlight the importance of incorporating goals of care, along with prognosis, into treatment plans [642]. The use of proactive family care conferences to identify advance directives and treatment goals within 72 h of ICU admission has been demonstrated to promote communication and understanding between the patient's family and the treating team; improve family satisfaction; decrease stress, anxiety, and depression in surviving relatives; facilitate end-of-life decision-making; and shorten ICU LOS for patients who die in the ICU [643,644]. Promoting shared-decision-making with patients and families is beneficial in ensuring appropriate care in the ICU and that futile care is avoided [641,645,646].…”
Section: U Setting Goals Of Carementioning
confidence: 99%
“…In general medical settings, ACP has been shown to increase patient and family satisfaction with care 10,11 and the likelihood that doctors and family members will understand and comply with patients' wishes for EOL care 10,[12][13][14] . It also increases the likelihood of a person dying in their preferred place, increases hospice use 14,15 , reduces hospitalisation 11,15 , leads to less 'aggressive' medical care at EOL 14,16,17 , and contributes to lower stress, anxiety and depression in surviving relatives 10,11,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Although there is some controversy regarding the effectiveness of written advance directive documents, 4 a systematic review and meta-analysis of English language randomized trials concluded that ACP interventions focused on discussions improved concordance between patients' preferences and end-of-life (EOL) treatment. 5 The Centers for Disease Control and Prevention reports that only 30% of U.S. adults have some form of advance care plan, 6 and low-income, minority, and low-literacy populations are the least likely to have engaged in ACP discussions or documentation. 7e9 The traditional approach to promote ACP is through clinic or hospital-based education.…”
Section: Introductionmentioning
confidence: 99%